Oysters in the land of cacao : archaeology, material culture, and societies at Islas de Los Cerros and the western Chontalpa, Tabasco, Mexico - Ensor, Bradley E., 1966- (Anthropological papers (Vermillion, S.D.), 2020)
This book delivers a presentation of the archaeology, material culture, and regional synthesis on the Formative to Late Classic period societies of the Western Chontalpa region (Tabasco, Mexico) through contemporary theory. It offers a significant new understanding of the Mesoamerican Gulf Coast. --